Safety key performance indicators for SMEs - Gholamkhasi, Arash (2014)
Today competitive market requires safer workplace and satisfied employees who highly improve quality and quantity of production. This may not possible without Occupational Safety and Health (OSH) programs that are utilized to handle hazardous circumstances. Trade-off between amount of incidents and related prevention costs seems to be more concerned while highly affects company profit. This study aims to determine safety key performance indicators which affect costing of occupational safety and health (OSH) in Small and Medium Enterprises (SMEs). Since recent 20 years, OSH has been used in many researches, but few studies have been done regarding SMEs. A literature survey was conducted to find the most critical key performance indicators. Key performance indicators were then evaluated using a questionnaire distributed among 30 SMEs located in Johor Bahru, Malaysia. A costing model, including wage of the safety staff as fixed cost and 17 variable costs is defined regarding to the indicators. As a result, suggested model clarified that training, ergonomic and technological indicators were the most effective factors.